Concussion Reporting and Safeguarding Policy Development in British American Football: An Essential Agenda - Travis, Eleanor; Thornton, Claire; Scott-Bell, Andrea (Frontiers in Sports and Active Living, 2021)
The objective of this study was to examine concussion reporting and safeguarding policy in British American Football (BAF). Data were collected via an online survey tool. The data presented are part of a broader study that examined injury profiles, concussion reporting behaviors, and medical provision in BAF. Concussion-like symptoms were found in over half (58.8%) of the participants. Of those, 36.4% reported they had previously been formally diagnosed with a concussion while playing BAF. Just under half of the participants (44.7%) had suspected they had had a concussion, although it was not formally diagnosed, and 23.5% of the participants had previously hidden concussion symptoms. Fifty-eight percent of the teams reported they did not have a regular game-day medic, with a range of hired medical personnel who attended the games. Prominent barriers to hiring a medic included budget, institutional support shortfall, and lack of medic reliability and game knowledge. BAF is a developing sport with a clear vision for growth of participation. Yet, the current concussion and medical provision policies do not address the sport's welfare needs. Through discussion of these policies in the context of this study's findings, we highlight vital areas of concern in policy and practice that the British American Football Association needs to address in their medical and concussion policies.